Colloidal cyst of the third ventricle. Case presentation - Ada Sánchez Lozano; María Octavina Rodríguez Roque; Joan O Rojas Fuentes (Medisur, 2009)
Colloidal cysts are congenital intracranial benign lesions of the anterior superior portion of the third ventricle. They represent between the 0,2 and 2 % of all the intracranial tumours and represent the 15 or 20 % of all the intraventricular masses. They become symptomatic during the adolescence or early adulthood and start normally with migraine or symptoms of intracranial hypertension causing obstructive hydrocephaly. We present the case of a teenager of 18 years of age with history of migraine after two years and the symptoms worsened in intensity and frequency including vomiting and bilateral paresthesia; the diagnosis was obstructive hydrocephaly with colloidal cyst of the third ventricle. An appropriate practice was adopted due to the uncertain diagnosis in order to avoid neurological damage and death. We discussed the main characteristics of the colloidal cyst, its clinical presentation and radiological characteristics and we performed.